2016
DOI: 10.4103/0972-0707.181925
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endodontics: Potential applications in clinical practice

Abstract: Contemporary endodontics has seen an unprecedented advance in technology and materials. This article aimed to review some of the challenges and advances in the following sections: (1) endodontic imaging, (2) root canal preparation, (3) root canal disinfection, (4) root canal filling, and (4) regenerative endodontic procedures (REPs). Jointly, these advances are aimed at improving the state of the art and science of root canal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 79 publications
3
45
0
8
Order By: Relevance
“…Those who combined different types of instrumentation treated 20 teeth or more. Our study consolidates the literature findings about the efficiency and speed of mechanical systems 5,24,25 .…”
Section: Discussionsupporting
confidence: 89%
“…Those who combined different types of instrumentation treated 20 teeth or more. Our study consolidates the literature findings about the efficiency and speed of mechanical systems 5,24,25 .…”
Section: Discussionsupporting
confidence: 89%
“…21,22 When complex anatomies are present, these inaccessible regions require greater reliance on debridement and disinfection techniques relative to the rest of the root canal system. 23 Complex anatomy also creates further procedural difficulties, which can leave debris and bacteria behind inadvertently. 3 Research demonstrates that bacteria remaining after endodontic therapy typically resides in complex anatomical regions, such as the lateral canals and isthmi.…”
Section: Resultsmentioning
confidence: 99%
“…[4] However, many studies have reported bacterial penetration through the entire length of the root canal within a few days following root canal filling with gutta-percha, which indicates that a perfect seal is hard to achieve in endodontic therapy. [56]…”
Section: Introductionmentioning
confidence: 99%